IDNLearn.com provides a reliable platform for finding accurate and timely answers. Ask any question and receive timely, accurate responses from our dedicated community of experts.
Sagot :
To prove by induction that for all positive integers [tex]\( n \)[/tex], [tex]\( 21 \mid \left(4^{n+1} + 5^{2n-1}\right) \)[/tex], we follow these steps:
### Base Case
Let's check the base case when [tex]\( n = 1 \)[/tex]:
[tex]\[ 4^{n+1} + 5^{2n-1} = 4^{1+1} + 5^{2 \cdot 1 - 1} = 4^2 + 5^1 = 16 + 5 = 21 \][/tex]
Since [tex]\( 21 \)[/tex] is divisible by [tex]\( 21 \)[/tex]:
[tex]\[ 21 \mid 21 \][/tex]
The base case holds true.
### Inductive Step
Next, we assume that the proposition is true for some positive integer [tex]\( k \)[/tex]. That is, we assume:
[tex]\[ 21 \mid \left( 4^{k+1} + 5^{2k-1} \right) \][/tex]
This is our induction hypothesis.
We need to prove that the proposition is true for [tex]\( k+1 \)[/tex], i.e., we need to show:
[tex]\[ 21 \mid \left( 4^{(k+1)+1} + 5^{2(k+1)-1} \right) \][/tex]
Simplify the expression:
[tex]\[ 4^{(k+1)+1} + 5^{2(k+1)-1} = 4^{k+2} + 5^{2k+1} \][/tex]
We need to show that [tex]\( 4^{k+2} + 5^{2k+1} \)[/tex] is divisible by [tex]\( 21 \)[/tex].
Express [tex]\( 4^{k+2} \)[/tex] in terms of [tex]\( 4^{k+1} \)[/tex]:
[tex]\[ 4^{k+2} = 4 \cdot 4^{k+1} \][/tex]
Similarly, express [tex]\( 5^{2k+1} \)[/tex] in terms of [tex]\( 5^{2k-1} \)[/tex]:
[tex]\[ 5^{2k+1} = 25 \cdot 5^{2k-1} \][/tex]
Thus, our problem reduces to:
[tex]\[ 4^{k+2} + 5^{2k+1} = 4 \cdot 4^{k+1} + 25 \cdot 5^{2k-1} \][/tex]
Using our induction hypothesis [tex]\( 21 \mid \left( 4^{k+1} + 5^{2k-1} \right) \)[/tex]:
[tex]\[ 4^{k+1} + 5^{2k-1} = 21m \quad \text{for some integer } m \][/tex]
We need to find a way to express [tex]\( 4 \cdot 4^{k+1} + 25 \cdot 5^{2k-1} \)[/tex] in terms of [tex]\( 21 \)[/tex]. Using the fact that:
[tex]\[ 4^{k+1} \equiv -5^{2k-1} \pmod{21} \][/tex]
By substitution [tex]\( 4 \cdot 4^{k+1} \equiv 4 \cdot (-5^{2k-1}) = -4 \cdot 5^{2k-1} \pmod{21} \)[/tex]:
[tex]\[ \Rightarrow 4 \cdot 4^{k+1} \equiv 4 \cdot 4^{k+1} \pmod{21} \][/tex]
Similarly for [tex]\( 25 \cdot 5^{2k-1} \)[/tex]:
[tex]\[ 25 \equiv 4 \pmod{21}, \][/tex]
so
[tex]\[ 25 \cdot 5^{2k-1} \equiv 4 \cdot 5^{2k-1} \pmod{21}. \][/tex]
Combining these results:
[tex]\[ 4 \cdot 4^{k+1} + 25 \cdot 5^{2k-1} \equiv 4 \cdot 4^{k+1} + 4 \cdot 5^{2k-1} \equiv 0 \pmod{21}. \][/tex]
Therefore,
[tex]\[ 21 \mid \left( 4^{(k+1)+1} + 5^{2(k+1)-1} \right) \][/tex]
Thus, by induction, for all positive integers [tex]\( n \)[/tex]:
[tex]\[ 21 \mid \left( 4^{n+1} + 5^{2n-1} \right) \][/tex]
This concludes the proof by mathematical induction.
### Base Case
Let's check the base case when [tex]\( n = 1 \)[/tex]:
[tex]\[ 4^{n+1} + 5^{2n-1} = 4^{1+1} + 5^{2 \cdot 1 - 1} = 4^2 + 5^1 = 16 + 5 = 21 \][/tex]
Since [tex]\( 21 \)[/tex] is divisible by [tex]\( 21 \)[/tex]:
[tex]\[ 21 \mid 21 \][/tex]
The base case holds true.
### Inductive Step
Next, we assume that the proposition is true for some positive integer [tex]\( k \)[/tex]. That is, we assume:
[tex]\[ 21 \mid \left( 4^{k+1} + 5^{2k-1} \right) \][/tex]
This is our induction hypothesis.
We need to prove that the proposition is true for [tex]\( k+1 \)[/tex], i.e., we need to show:
[tex]\[ 21 \mid \left( 4^{(k+1)+1} + 5^{2(k+1)-1} \right) \][/tex]
Simplify the expression:
[tex]\[ 4^{(k+1)+1} + 5^{2(k+1)-1} = 4^{k+2} + 5^{2k+1} \][/tex]
We need to show that [tex]\( 4^{k+2} + 5^{2k+1} \)[/tex] is divisible by [tex]\( 21 \)[/tex].
Express [tex]\( 4^{k+2} \)[/tex] in terms of [tex]\( 4^{k+1} \)[/tex]:
[tex]\[ 4^{k+2} = 4 \cdot 4^{k+1} \][/tex]
Similarly, express [tex]\( 5^{2k+1} \)[/tex] in terms of [tex]\( 5^{2k-1} \)[/tex]:
[tex]\[ 5^{2k+1} = 25 \cdot 5^{2k-1} \][/tex]
Thus, our problem reduces to:
[tex]\[ 4^{k+2} + 5^{2k+1} = 4 \cdot 4^{k+1} + 25 \cdot 5^{2k-1} \][/tex]
Using our induction hypothesis [tex]\( 21 \mid \left( 4^{k+1} + 5^{2k-1} \right) \)[/tex]:
[tex]\[ 4^{k+1} + 5^{2k-1} = 21m \quad \text{for some integer } m \][/tex]
We need to find a way to express [tex]\( 4 \cdot 4^{k+1} + 25 \cdot 5^{2k-1} \)[/tex] in terms of [tex]\( 21 \)[/tex]. Using the fact that:
[tex]\[ 4^{k+1} \equiv -5^{2k-1} \pmod{21} \][/tex]
By substitution [tex]\( 4 \cdot 4^{k+1} \equiv 4 \cdot (-5^{2k-1}) = -4 \cdot 5^{2k-1} \pmod{21} \)[/tex]:
[tex]\[ \Rightarrow 4 \cdot 4^{k+1} \equiv 4 \cdot 4^{k+1} \pmod{21} \][/tex]
Similarly for [tex]\( 25 \cdot 5^{2k-1} \)[/tex]:
[tex]\[ 25 \equiv 4 \pmod{21}, \][/tex]
so
[tex]\[ 25 \cdot 5^{2k-1} \equiv 4 \cdot 5^{2k-1} \pmod{21}. \][/tex]
Combining these results:
[tex]\[ 4 \cdot 4^{k+1} + 25 \cdot 5^{2k-1} \equiv 4 \cdot 4^{k+1} + 4 \cdot 5^{2k-1} \equiv 0 \pmod{21}. \][/tex]
Therefore,
[tex]\[ 21 \mid \left( 4^{(k+1)+1} + 5^{2(k+1)-1} \right) \][/tex]
Thus, by induction, for all positive integers [tex]\( n \)[/tex]:
[tex]\[ 21 \mid \left( 4^{n+1} + 5^{2n-1} \right) \][/tex]
This concludes the proof by mathematical induction.
Thank you for using this platform to share and learn. Keep asking and answering. We appreciate every contribution you make. Find clear answers at IDNLearn.com. Thanks for stopping by, and come back for more reliable solutions.